2021
DOI: 10.1080/00071005.2021.1948501
|View full text |Cite
|
Sign up to set email alerts
|

International Students and Alternative Visions of Diaspora

Abstract: This paper explores the contemporary relationship between international student migration and diaspora formation. It argues that international students have been largely absent from recent discussions of 'knowledge diasporas', where migrants' 'home' states attempt to harness and co-opt the skills and knowledge of their émigrés. This is surprising, given students' evident role in knowledge circulation and exchange. In this paper, we foreground the significance of international students but also explore their re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 49 publications
0
13
0
1
Order By: Relevance
“…However, thus far, no studies have explored how the hukou system affects ISM, which is a quantitatively significant subgroup of international migrants, especially in relation to China, which sent out more than 700,000 students only in 2019 (National Bureau of Statistic of China NBSC, 2021). This gap in the research is remarkable because most developed Chinese cities, including Beijing and Shanghai, have designed specific hukou policies oriented toward returning international students in recent years, thus providing opportunities for them, in theory, to access hukou status in these developed regions (Brooks & Waters, 2021;Zhai, 2020). Therefore, accessing hukou status in developed Chinese cities via ISM could be a potential motivation for some Chinese people to engage in ISM, but there is no existing research on the scale or mechanics of this process.…”
Section: The Hukou System: An Institutional Barrier To Mobility Beyon...mentioning
confidence: 99%
See 2 more Smart Citations
“…However, thus far, no studies have explored how the hukou system affects ISM, which is a quantitatively significant subgroup of international migrants, especially in relation to China, which sent out more than 700,000 students only in 2019 (National Bureau of Statistic of China NBSC, 2021). This gap in the research is remarkable because most developed Chinese cities, including Beijing and Shanghai, have designed specific hukou policies oriented toward returning international students in recent years, thus providing opportunities for them, in theory, to access hukou status in these developed regions (Brooks & Waters, 2021;Zhai, 2020). Therefore, accessing hukou status in developed Chinese cities via ISM could be a potential motivation for some Chinese people to engage in ISM, but there is no existing research on the scale or mechanics of this process.…”
Section: The Hukou System: An Institutional Barrier To Mobility Beyon...mentioning
confidence: 99%
“…The Chinese hukou system has long been regarded as an institutional barrier to Chinese internal migration (Montgomery, 2012; Qian et al, 2020), and has diverse influences on Chinese internal migrants, especially regarding their employment (Song, 2014; Wang & Moffatt, 2008; Xiao & Bian, 2018; Zhang, 2020). However, only a few recent studies have observed that the hukou system influences the ISM experience of Chinese students (Brooks & Waters, 2021; Zhai, 2020). Brooks and Waters (2021) noted that certain cities provide hukou privileges for returning students, allowing them to access the best job opportunities in the most buoyant local labour markets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Larner (2015) identifies the increasing internationalisation of the academic labour market, proposing that diasporic academics have become central to the creation of global knowledge networks. Recently, Brooks and Waters (2021) and Han and Tong (2021) have argued that international students are part of the diaspora formation that participates in global knowledge circulation and reinvents the notion of brain drain. International students, simultaneously migrants and students, interact with various groups of people and communities across a myriad of social spaces.…”
Section: 2mentioning
confidence: 99%
“…In the case of the Chinese diaspora, it has often included ethnic Chinese immigrants, sojourners, and temporary migrants worldwide irrespective of their migration history and factual citizenship to encompass a complex transnational population [ 53 ]. Recently, scholars have also proposed international students as alternative visions of diaspora to maximize the empirical significance of this population in diasporic studies [ 54 ]. In the current research, we focus mainly on Chinese international students and expatriates as the population under study.…”
Section: Introductionmentioning
confidence: 99%